Nursing leadership training: A scoping review - Yanthi, Kadek Ayu Purnama; Eka, Ni Gusti Ayu; Manalu, Enjelika Putri; Paiuk, Erica Dorelia; Sinurat, Kyela Friska Br (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Nursing leadership training is essential for preparing nurses to lead teams, make strategic decisions, and adapt to rapidly evolving healthcare environments. Despite its critical role, the effectiveness of leadership programs is often undermined by various challenges, including limited institutional support, high workload demands, resource constraints, and cultural or psychological barriers. These issues can impact program outcomes and the long-term development of nursing leadership capacity. Purpose: To explore the design and implementation challenges of nursing leadership training programs. Method: This scoping review followed the Joanna Briggs Institute (JBI) guideline. Searching was conducted using three databases including Medline (Ebsco), ScienceDirect (Elsevier), and PubMed. Inclusion and exclusion criteria guided study selection. Data from 14 peer-reviewed articles published between 2021 and 2024 were extracted and synthesized using content analysis and descriptive statistics. Results: Four major themes were identified organizational barriers, individual barriers, non-interventional programs, and interventional programs each with sub-themes. Effective leadership interventions have emerged across several forms: mentorship, simulation, empowerment programs, and structured curricula. Conclusion: Nursing leadership training must shift from conceptual frameworks to evidence-based, context-specific interventions. Strengthening organizational infrastructure, promoting inclusivity, and enhancing program clarity and evaluation are critical for building effective, scalable, and sustainable leadership pathways in nursing.